2022
DOI: 10.3390/children9101548
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Generalized Anxiety Disorder According to Frequent Sedentary Times Based on the 16th Korea Youth Risk Behavior Web-Based Survey

Abstract: This study aimed to identify the association between sedentary behavior and anxiety disorders in 53,510 Korean adolescents. It analyzed data from the 16th (2020) Korea Youth Risk Behavior Web-based Survey (KYRBS). The dependent variable was the generalized anxiety disorder-7 (GAD-7). The GAD-7 scores were divided into normal, mild, moderate, and severe levels. The independent variables were sedentary time for learning, other sedentary times, total sedentary time, and regular physical activity. The confounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…As in previous studies, it is clear that an increase in sedentary behavior is significantly associated with GAD. 13 16 However, unlike sedentary time, regular PA was not significantly related to GAD levels in our previous study. Previous studies have shown that regular PA or moderate levels of exercise help alleviate anxiety disorders 13 16 ; however, our study did not reveal this.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…As in previous studies, it is clear that an increase in sedentary behavior is significantly associated with GAD. 13 16 However, unlike sedentary time, regular PA was not significantly related to GAD levels in our previous study. Previous studies have shown that regular PA or moderate levels of exercise help alleviate anxiety disorders 13 16 ; however, our study did not reveal this.…”
Section: Discussionmentioning
confidence: 53%
“… 13 16 However, unlike sedentary time, regular PA was not significantly related to GAD levels in our previous study. Previous studies have shown that regular PA or moderate levels of exercise help alleviate anxiety disorders 13 16 ; however, our study did not reveal this. A previous study reported a significant negative correlation between GAD-7 scores and PA through multiple regression analysis; vigorous PA and strength exercises were more effective in preventing GAD than mild PA. 13 However, they only divided PA into three types and did not provide specific information such as intensity, time, and frequency.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…또한 좌식행동 과 불안장애의 관련성 연구는 성인을 대상으로 활발하게 진행 되어 왔으며 [17] 한국 청소년을 대상으로 확인한 연구는 매우 부족하다. 최근 국내 청소년을 대상으로 좌식행동과 범불안장 애 관계를 확인한 연구결과에 따르면 학습의 좌식행동, 학습 외 좌식행동, 좌식행동을 위한 총 시간이 범불안장애와 연관성 이 있는 것으로 보고되었다 [18]. 하지만…”
unclassified